ANALISIS PENGARUH MARKET CAPITALIZATION TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Amanda Wahyu Nuraningrum; Dyah Fitriani (Universitas Ahmad Dahlan, 2013)
This study aimed at testing and analyzing how both the big market capitalization and the small one had an effect on the price stock. The population of this study was all companies listed in BEI in the period of 2007 – 2011. The purposive sampling with a quota sampling was applied in the technique as sampling, while the selection result of sampling was 36 companies with big market capitalization and 36 companies with small market capitalization. The method of data selection of this study was documentation because the data was taken from other sides. The dependent variable used in this study was price stock and the independent variable was market capitalization. The tools for data analysis applied Vector Error Correction Model (VECM). The result of this study indicated that the big market capitalization had a positive effect on the price stock and gave an effect of 69.91% on the price stock at the end of the period. While the small market capitalization had a positive effect on the price stock at 85.09%.